Supported employment and disabled people in New Zealand : from assimilation to transformation : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University - Bennie, Garth; Bennie, Garth (Massey University, 1996)
This thesis examines the development and current status of supported employment, a relatively recent concept that holds much promise for improving the employment prospects of disabled people. It argues that supported employment offers a positive departure from the poor performance of traditional approaches to vocational rehabilitation and job placement. However the thesis demonstrates that because of the perspectives which inform the current concept of supported employment it can be disempowering and oppressive. The origins and current status of supported employment are explored to identify the central issues and concerns. The capacity and limits of supported employment in the broader arena of employment support services in New Zealand are revealed. The theoretical orientation of the thesis lies in the critical tradition. Three perspectives that have influenced policies and practices in the disability arena are examined The views and experiences of fourteen disabled people on the nature and performance of employment support services were obtained through individual interviews in order to reveal the central issues as defined by service users. Many of these people were also involved with the disability rights movement. The findings revealed a great deal of concern about the effectiveness of employment support services. In particular participants identified disabled people's lack of power in the development and use of services. A policy analysis of employment support services, a critical theoretical analysis of disability and the reflections of a group of service users contribute to the reconstruction of supported employment. An emancipatory model of supported employment is described in which disabled people are empowered to reveal the contradictions and power imbalances of conventional approaches to vocational rehabilitation and job placement. As a result employment support services and related policies are challenged to shift from a focus on assimilation in the workplace to the transformation of workplaces and employment support services in disabled people's interests.
Keywords: Employment; Vocational rehabilitation; Support services; Disability rights